2020
DOI: 10.1021/acs.jpcc.0c00423
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Bound Water on Cotton Surfaces by Atomic Force Microscopy and Atomic Force Microscopy–Infrared Spectroscopy

Abstract: A wet cotton rag becomes stiff after natural drying. We propose a model for this hardening phenomenon, which explains that the stiffness of cotton is caused by a cross-linked network between single fibers, mediated by capillary adhesion of bound water on the surface of cellulose. Here, with the aid of atomic force microscopy and atomic force microscopy−infrared spectroscopy, we reveal the existence of the bound water on the surface of a cotton single fiber under naturally dried conditions. We also find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 50 publications
3
24
1
Order By: Relevance
“… 30 , 31 For RH ≤ 40%, adsorption is dominated by Van der Waals forces for most materials and rapidly increases with RH due to the increase in F c . 30 32 The magnitude of F c is also a function of particle size, where F c scales linearly with particle size, shown in eq 3 η represents the surface tension of H 2 O. 30 , 31 , 33 35 The surface hydrophilicity also impacts F c , with increased adhesion for hydrophilic surfaces (e.g., cotton and rayon) and is absent for hydrophobic surfaces (e.g., polyester and polypropylene) where H 2 O uptake is negligible even at high RH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 , 31 For RH ≤ 40%, adsorption is dominated by Van der Waals forces for most materials and rapidly increases with RH due to the increase in F c . 30 32 The magnitude of F c is also a function of particle size, where F c scales linearly with particle size, shown in eq 3 η represents the surface tension of H 2 O. 30 , 31 , 33 35 The surface hydrophilicity also impacts F c , with increased adhesion for hydrophilic surfaces (e.g., cotton and rayon) and is absent for hydrophobic surfaces (e.g., polyester and polypropylene) where H 2 O uptake is negligible even at high RH.…”
Section: Resultsmentioning
confidence: 99%
“… 30 , 31 , 33 35 The surface hydrophilicity also impacts F c , with increased adhesion for hydrophilic surfaces (e.g., cotton and rayon) and is absent for hydrophobic surfaces (e.g., polyester and polypropylene) where H 2 O uptake is negligible even at high RH. 32 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…As compared to bulk IR spectroscopy, nanoscale IR spectroscopy has great potential for an in-depth analysis of the mechanism of interactions between CNMs and small molecules, such as water [ 49 ]. Figure 3 a shows slight differences of the OH-stretch band in the 3800–2600 cm −1 region in the conventional ART-IR spectra between different dried cotton cellulose.…”
Section: Afm-ir and Ir S-snom Application In Cellulose Materialsmentioning
confidence: 99%
“… ( a ) Conventional ATR-IR spectra of dried cotton cellulose; ( b ) Direct observation of the interaction between water and cellulose by AFM-IR. Reproduced with permission from [ 49 ]. Copyright American Chemical Society, 2020.…”
Section: Figurementioning
confidence: 99%
“…In their mechanism, the existence of water at the cotton fiber is important but it was not verified experimentally. Recently, Igarashi et al 15 reported that bound water, which has a pseudo liquid property, exists at the surface of a cotton fiber by using atomic force microscopy (AFM) and atomic force microscopybased infrared spectroscopy (AFM-IR). The water with the pseudo liquid property has been known to have higher viscosity, dependent on the condition 16 (the viscosity of bulk water is 0.89 mPaÁs), and that of pseudo liquid water is known to be greater.…”
Section: Introductionmentioning
confidence: 99%